Strategies for fostering inclusive classrooms in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Bingley, U.K. : Emerald Publishing Limited, 2019)
Higher education institutions continue to address an increasingly complex set of issues regarding equity, diversity and inclusion. Many institutions face mounting pressure to find innovative solutions to eliminate access, participation, and achievement barriers as well as practices that impede retention and graduation rates in higher education. This volume provides educators with a global understanding of the challenges associated with the growing diversity of student identities in higher education and provides evidence-based strategies for addressing the challenges associated with implementing equity and inclusion at different higher education institutions around the world.
Prelims -- Part I Concepts and principles -- Introduction to strategies for fostering inclusive classrooms in higher education -- Part II Global practices and challenges -- Chapter 1: Global perspectives on academic integrity -- Chapter 2: Valuing knowledge(s) and cultivating confidence: contributions of student-faculty pedagogical partnerships to epistemic justice -- Chapter 3: Cultural mediation pedagogy and its ability to enable bridge-building between two coexisting groups that do not meet -- Chapter 4: The minimal link of a thing in common: a framework for academic outreach in widening participation in Australia -- Chapter 5: Decolonizing the classroom in social justice learning: perspectives on access and inclusion for participants living with disabilities -- Chapter 6: Rethinking the support programmes for the marginalised students in higher education through the lens of social justice -- Chapter 7: Innovating curriculum: integrating global citizenship and equity education for student success -- Chapter 8: An equity-based model of teaching and learning: bridging the academic literacy skills divide in the english classroom in South Africa -- Chapter 9: Service-learning as a methodology to promote equity and inclusion: best practice experience in Ecuador -- Chapter 10 The role of educational technology in promoting the inclusion of rural clinical schools for ophthalmology teaching using virtual patients -- Chapter 11 Toward a transformative transition: a critical pedagogical approach to social-psychological interventions in first-year seminar -- Chapter 12 Considerations for using critical pedagogy as the vehicle to promote social justice in higher education -- Chapter 13 Online: a new geography' of learning that supports female access to higher education -- Chapter 14 Adopting the international standard becoming a human-centred organization (ISO 27500)' supports a strategic approach to internationalisation -- Chapter 15 Improving inclusive learning through technology mediated co-inquiry -- About the authors -- Name index -- Subject index.
Includes indexes.
Print version record
Keywords: People with disabilities -- Education (Higher); Inclusive education; Education -- Higher; Educational strategies & policy